The Community Health Worker academy: a novel healthcare and public health workforce development model - McCaughtry, Nate; Somers, Cheryl L. (Frontiers in Health Services, 2025)
As the demand for an expanded Community Health Worker (CHW) workforce accelerates nationwide, the need for training, continuing education, professional development, and experiential field placements (internships and apprenticeships) with quality supervision has expanded dramatically. For example, the US state of Michigan recently received federal approval for the health education and social determinants of health services provided by CHWs to be eligible for Medicaid insurance reimbursement (governmental subsidized healthcare insurance), which has spurred tremendous demand for the CHW workforce by all types of employers. This paper describes a series of events and opportunities that led to the development of the Wayne State University Community Health Worker Academy (CHWA) in Detroit, Michigan, USA. Preliminary evidence suggests that the Academy's model and continuous process improvement strategies are successful. Implications of this model for other organizations involved in expanding and strengthening the CHW workforce development nationally and internationally are discussed, as are implications for career pathway opportunities for CHWs beyond their initial certification.